Taxonomic study of the leafhopper genus Oncopsis (Hemiptera, Cicadellidae, Macropsinae) from Sichuan Province, China with description of two new species and a key to males - Hu Li; Juan Li; Ren-Huai Dai (ZooKeys, 2019)
This paper deals with the leafhopper genus Oncopsis (Macropsinae) from Sichuan Province of China, and describes and illustrates two new species, O. konkaensis sp. nov. from Minya Konka (Sichuan), and O. moxiensis sp. nov. from Moxi Town (Sichuan), and provides a key to males and a geographic distribution map for Oncopsis species from Sichuan.